Covid-19's lessons for standard building design: Proinfância daycare centers - Fontes, Andréa dos Reis; Imbronito, Maria Isabel (Revista Nacional de Gerenciamento de Cidades, 2023)
The Covid-19 pandemic brought changes in the behavior of society, with the suspension of several activities, among them the access of children to schools. This study has as main objective the analysis of the daycare spaces of the Proinfância program regarding the attendance of environmental comfort, dimensioning and salubrity, considering the set of issues brought by the pandemic. To achieve this purpose, analyses were made of the type C Proinfância building, project used in the construction of the school unit chosen as case study: the Unidade Municipal de Educação Infantil Profª Júlia Maria de Almeida Oliveira, in the city of Lagarto, Sergipe. The secondary objectives are: to analyze the specificities of the implementation of this standard building in Lagarto and to analyze the post-occupancy condition during and after the Covid-19 pandemic. The methodological approach of the study is quali-qualitative type, applied on documents provided by the Proinfância website and complemented by case study, with detailing of techniques and procedures to achieve the proposed objectives. The study explores the POE methodology (Post-Occupancy Evaluation) for the object of study, selecting the universe of tools to be applied. These are: walkthrough analysis, study of recommendations and technical analysis by the researcher.